2018
DOI: 10.1002/jsde.12037
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Foam Self‐Generation Using In Situ Carbon Dioxide (CO2) for Enhancing Oil Recovery

Abstract: In situ carbon dioxide (CO2) foam flooding has proved to be economically feasible in the oil field, but its self‐generation behavior in the bulk scale/porous media is far from understood. In this study, the optimum in situ CO2‐foaming agent was first screened, and then in situ foam was investigated in the bulk. In situ foam flooding was conducted to evaluate the displacement characteristics and enhanced oil recovery of this system. The results showed that the foaming agent comprising 0.5% sodium dodecyl sulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In contrast, the ISGF foam was more uniform and denser (Figure ), which may come from the homogeneous distribution of the bubbles created by the in situ reaction. Homogeneous sizes of foam can effectively prevent coarsening and prolong the life of the foam …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the ISGF foam was more uniform and denser (Figure ), which may come from the homogeneous distribution of the bubbles created by the in situ reaction. Homogeneous sizes of foam can effectively prevent coarsening and prolong the life of the foam …”
Section: Resultsmentioning
confidence: 99%
“…a, after 0.15 PV CO 2 producer solution (10% AB) and 0.1 PV releasing agent (5% AC‐2+ 5% AA (volume ratio, 4:1)) containing the foam agent were successively injected, foam gradually formed and displaced the oil. With the increase of foam volume, foam propagated downward and forward (the IFT between in situ foam system and crude oil was 0.048 mN m −1 ; the foam properties were investigated in our previous study, the foam volume was 171 mL, the half‐life of in situ CO 2 foam was 62 min (Jin et al, )). In SWF, water entered the rich oil area with less foam, resulting in the enhancement of swept area and oil recovery.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain a sustained‐release system with high CO 2 production efficiency and low CO 2 production rate, a compound sustained‐release system was optimized in a previous study and the results are shown in Fig. (Jin et al, ). For the SA/HA system, when the SA/HA weight ratio was less than 7/1, the system had no sustained‐release property.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to overcome these problems and expand the foam application, in situ CO 2 foam method has been sought to replace the current conventional injection method. The potential benefits of this new method mainly including the following three aspects: (a) equipment and material aspect, ISCF system does not rely on the transportation pipeline and natural CO 2 source . Besides traditional foam injection equipment requires high pressure capacity, ISCF can reduce the dependence on high pressure equipment, which contributes to the application and promotion in offshore oil fields.…”
Section: Introductionmentioning
confidence: 99%
“…The potential benefits of this new method mainly including the following three aspects: (a) equipment and material aspect, ISCF system does not rely on the transportation pipeline and natural CO 2 source. 33,34 Besides traditional foam injection equipment requires high pressure capacity, ISCF can reduce the dependence on high pressure equipment, which contributes to the application and promotion in offshore oil fields. (b) Injection effect aspect, ISCF not only has better swept volume and cleaning efficiency than gas flooding, water alternating gas (WAG) flooding and carbonated water injection (CWI), but also unblock the contaminated formation to some extent.…”
mentioning
confidence: 99%